Síndrome de Budd Chiari como complicación de cáncer renal. Reporte de dos casos. - SALINAS, César; CASAVILCA ZAMBRANO, Sandro; ARENAS, José Luis; GUERRERO, Carlos (Revista Médica Herediana, 2013)
We report two cases of patients, that had a clinical feature, with jaundice, headache, and sensorial compromise, swelling of low extremities and ascites. The necropsy had shown in both cases, renal clear cell carcinoma, with tumoral trombosis of the renal vein, inferior cava vein and superior hepatics veins; that provoked post hepatic portal hypertension with necrosis centrilobular, bleeding and hepatic encephalopathy. This cases show the relation between renal carcinoma and Budd Chiari syndrome.